Extracellular matrix of galectin-1-exposed dermal and tumor-associated fibroblasts favors growth of human umbilical vein endothelial cells in vitro: a short report - Peržeľová, Vlasta; Varinská, Lenka; Dvořánková, Barbora; Szabo, Pavol; Spurný, Peter; Valach, Jaroslav; Mojžiš, Ján; André, Sabine; Gabius, Hans-Joachim; Smetana, Karel; Gál, Peter (Anticancer research, 2014)
BACKGROUND/AIM: Stromal cells in the tumor microenvironment are primarily considered as sources of promalignant factors. The objective of our study was to define the effect of extracellular matrix (ECM) produced by normal dermal or cancer-associated fibroblasts exposed to adhesion/growth-regulatory lectin galectin-1 on human umbilical vein endothelial cells (HUVECs). MATERIALS AND METHODS: Fibroblasts were cultured for 10 days with lectin, followed by removing cellular constituents after an osmotic shock. Freshly-isolated HUVECs were placed on the ECM. In parallel, HUVECs were seeded on untreated and gelatin-coated surfaces as controls. A positive control for growth of HUVECs culture using medium supplemented with vascular endothelial growth factor completed the test panel. Cells were kept in contact to the substratum for two days and then processed for immunocytochemistry. RESULTS: HUVECs seeded on fibroblast-generated ECM presented a comparatively high degree of proliferation. Furthermore, contact to substratum produced by tumor-associated fibroblasts led to generation of a meshwork especially rich in fibronectin. CONCLUSION: Galectin-1 is apparently capable to trigger ECM production favorable for growth of HUVECs, prompting further work on characterizing structural features of the ECM and in situ correlation of lectin presence, ECM constitution and neoangiogenesis.
Keywords: wound healing; Tumor Microenvironment; proliferace buněk; Galectin 1; tumor growth; Humans; Cells, Cultured; Fibroblasts; Extracellular Matrix; nádorové mikroprostředí; fibroblasty; lidé; galektin 1; endoteliální buňky pupečníkové žíly (lidské); Cell Proliferation; Vascular Endothelial Growth Factor A; Angiogenesis; vaskulární endoteliální růstový faktor A; lectin; kultivované buňky; Human Umbilical Vein Endothelial Cells; extracelulární matrix; extracellular matrix